Legal maxim “every loan that brings benefit is usury”: its related issues and implementation in financial transactions - Amanullah, Muhammad; Zakariyah, Luqman (2017)
A number of Islamic legal maxims are related to transactions (fiqh al-mu‘ᾱmalᾱt) and they could be implemented in Islamic finance and banking. One of these maxims is “Every loan that brings benefit is usury” (Kullu qarḍ Jarra Manf‘atan fahuwa Ribᾱ’). A normal ruling of the Sharῑ‘ah is that if anyone receives loan from a person or a bank, he is supposed to return its exact amount to the moneylender without any increase in it. Any increase, whether it is in the form of money, goods or any other assistance, is considered usury (ribᾱ’) and therefore it is forbidden. However, jurists have disputed over the issue: “If this increase is not mentioned at the time of giving the loan as its condition, and the borrower gives it at the time of paying the loan back to the moneylender or before it.” Some of them maintain that it is lawful, while some others consider it as forbidden. Using descriptive and analytical methods, this paper will discuss the above legal maxim, its proofs, disputes of jurists on its related issues and will try to give preference to the opinion which is stronger based on the strength of the proofs. Then it will strive to discuss implementation of this maxim on some pre-Islamic and contemporary financial transactions in Malaysia.